Conforto e desconforto de passageiros em cabines de aeronaves - Greghi, Marina Fonseca (2012)
Comfort is a subject matter that is gaining relevance in the aviation industry, taking into consideration the necessity of the manufactures, as well as the airlines, in differentiating themselves in a market far more competitive. Nevertheless, comfort is a subjective experience, affected by many factors (psychological, physical and physiological) and a reaction of the environment. Therefore the case studies about the theme highlight a difficulty to analyze all the variable that interfere in the perception of comfort and discomfort, mainly when it comes to aircraft cabins. The general objective of this case study was to identify the variables related to comfort and discomfort in airplane cabins, through the passengers analysis of the activity in use situations, in order to develop a model for the assessment of comfort and discomfort. The case study was undertaken in 36 Brazilian airports and during 40 segments in corporate domestic flights, and the data collection adopted were: 377 questionnaires in airports and 291 in-flight questionnaires, 44 postures records and actions and also 12 semi-structured interviews. The data collected through the questionnaire were statistically analyzed and the ones obtained by systematic observations were analyzed and reinstated in the participants selfconfrontation interviews. One verified that the passengers most frequent activities are: feeding (91,1%), resting and sleeping (82,3%), reading, writing and working (80,5%), entertaining activities (56,1%), as well as, going to the toilet (54,8%). Out of those activities, the one which is harder for the passengers is resting and sleeping (74,6). From the analysis of the difficulties regarding every single activity, one verified that the variables related to space, as leg-room, personal area, as well as, the physical space for the movement of the body are the critical variable mentioned by the passengers. The crew service and also the entertainment on board were considered as well once they can produce comfort. One of the results of this case-study was the proposal of a methodology that led to envelops of postures with the calculation of the passengers area in use during their action, which can be a useful tool in the process of aircraft cabins project when making possible the calculation of the space for the action with base in the rebuilt course. In relation to the model of comfort and discomfort, a proposal was elaborated having the passengers action as a mediator. The proposed model parts from the premise that comfort and discomfort should be considered as two dimensions separated from experience, that feature different determinants (Zhang et al., 1996) and that the activity, in particular, the possibility and/or impossibility of acting, is in a mediator element between comfort and discomfort, being able to interfere in that relationship. From this case study have been developed one conceptual model and a methodology to analyze the comfort- the activity analysis is the main element of the model. Besides that, the database created in this study can be considered one tool to be use by the engineers, while they can use during the development of the project, in order to generate knowledge to the user.